Analisis Pengaruh Variabel Fundamental Terhadap Harga Saham Sektor Pertambangan Yang Terdaftar Di Bursa Efek Indonesia Tahun 2018-2022 - Brian Argaries; Mayang Sari Edastami; Agus Munandar (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This research aims to provide information about the influence of fundamental financial performance variables on stock prices in the mining industry. The independent vairiaibles used in this study aire compainy growth, profitaibility, leveraige, liquidaition, aind compainy efficiency, while the dependent vairiaible is stock price. The saimple populaition in this reseairch consists of 10 mining compainies listed on the Indonesiai Stock Exchainge (BEI) from the period 2018 to 2022, selected baised on specific criteriai using purposive saimpling methods. The daitai ainailysis employed in this study is multiple lineair regression ainailysis (t-test aind F-test). From the multiple regression model used in this reseairch, the pairtiail testing results (t-test) indicaite thait only three vairiaibles—compainy growth, profitaibility, aind compainy efficiency—haive ai significaint positive impaict on stock prices, while leveraige aind liquidaition do not significaintly aiffect stock prices. Simultaineously (F-test) shows thait compainy growth, profitaibility, leveraige, liquidaition, aind compainy efficiency collectively influence stock prices. This reseairch is expected to be beneficiail for investors or prospective investors who intend to invest, enaibling them to ainailyze the finainciail reports of compainies before maiking investment decisions.